A Structural Equation Model for the Study of Sustainable Performance by Private Universities in Malaysia. - Basu Govindaraju; John Jeyasingam; Mamun Habib; Uvarani Letchmana; Sasidevi Ratnam (International Journal of Supply Chain Management, 2019)
Abstract - This empirical study employed structural equation modeling (SEM) to investigate the impact of sustainable practices on sustainable performance of higher education institutions. Firstly, the sustainable performance survey is designed to investigate its main influencing factors among the pool of constructs includes; economic, environment, social and top management support factors. Secondly, based on the SEM, the levels of sustainable performance of the universities are quantified in accordance with factors. The findings were supported by empirical evidence, as the study established that only economic and environment factors have significant positive relationship and impact sustainability performance. This paper provides a greater understanding of the interactions between key elements of sustainable practices associated with university performance provision as well as the degree of relationship between them.